Religion and stock price crash risk: Evidence from China - Wenfei Li; Guilong Cai (China Journal of Accounting Research, 2016)
This paper investigates whether religious traditions influence firm-specific crash risk in China. Using a sample of A-share listed firms from 2003 to 2013, we provide evidence that the more intense the religious environment, the lower the stock price crash risk, implying that religion plays an important role in Chinese corporate governance. Further, we find that (1) religion affects stock price crash risk by reducing earnings management and the management perk problem; (2) different religions have different effects, and Taoism, in particular, is unrelated to crash risk; and (3) the effects of religion are more pronounced with higher quality corporate governance and a stronger legal environment. Religion constrains the management agency problem, thus reducing stock price crash risk in China. Our paper enriches the literature on stock price crash risk and religion, and on new economic geography.
Keywords: 650; Religious environment; Stock price crash risk; Informal institution; Corporate governance